System bankowy a gospodarka finansowa miasta - Wartalska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this article is to generally specify the problems of co-operation of banks and the city as territorial self-governed units. The beginning of co-operation of banks and territorial self-governed units was difficult. From one side banks did not have specified offer for cities or procedures that banks had, were to complicated. From another side, bank employees complained on disability of self- governed authorities to specify detailed unit's needs. Nowadays, with constant and fast development of bank services grows the number of high-level financial instruments for self-governments. These instruments are being developed and modernized constantly, In times of close co-operation, many financial institutions offer broad advisory services for choosing (by the city) the best financial source for given investment; concept preparation for getting relatively less expensive financial sources as well as for the appraisal of profitability of development projects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 507-517